2021
DOI: 10.1016/j.jsxm.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Genitourinary Syndrome of Menopause and 3D High-Frequency Endovaginal Ultrasound Measurement of Vaginal Wall Thickness

Abstract: Background To date, there is no certain method for diagnosis of genitourinary syndrome of menopause (GSM) and vaginal atrophy. Aim We aim to evaluate vaginal wall thickness (VWT) using 3D high frequency endovaginal ultrasound (3D EVUS) in GSM and also to investigate whether there is any association between VWT and postmenopausal sexual dysfunction. Methods Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…As vaginal wall thinning is a real phenomenon in the GSM, ultrasound measurement of vaginal wall thickness has been proposed as a potential biomarker of vaginal health. In fact, some authors have advocated this measurement using ultrasound 5–11 . However, we observed that there is no standardized approach for measuring vaginal wall thickness.…”
Section: Introductionmentioning
confidence: 86%
“…As vaginal wall thinning is a real phenomenon in the GSM, ultrasound measurement of vaginal wall thickness has been proposed as a potential biomarker of vaginal health. In fact, some authors have advocated this measurement using ultrasound 5–11 . However, we observed that there is no standardized approach for measuring vaginal wall thickness.…”
Section: Introductionmentioning
confidence: 86%
“…20 The other is using 3D endovaginal probe to measure the anterior and posterior walls separately. 21 These methods can be applicable for research purposes, however 2D transabdominal ultrasonography is widely used and the described technique is easy to learn. The method is also acceptable for the patient since it does not require any vaginal intervention which can be painful for women with vaginal atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…One of these is using in vivo microscopy to measure the distance between the subepithelial microcirculation and the epithelial surface 20 . The other is using 3D endovaginal probe to measure the anterior and posterior walls separately 21 . These methods can be applicable for research purposes, however 2D transabdominal ultrasonography is widely used and the described technique is easy to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal ultrasound has been piloted to measure vaginal mucosa and vaginal wall thickness in postmenopausal women. 7 Differences in thickness were noted and correlated with GSM symptoms in women with and without GSM as defined by the Vaginal Health Index. Transvaginal ultrasound measurements have been correlated with histology of pelvic floor structures.…”
mentioning
confidence: 97%
“…Techniques used in research of pelvic floor disorders and sexual medicine research offer new possibilities for assessing these factors. Transvaginal ultrasound has been piloted to measure vaginal mucosa and vaginal wall thickness in postmenopausal women 7 . Differences in thickness were noted and correlated with GSM symptoms in women with and without GSM as defined by the Vaginal Health Index.…”
mentioning
confidence: 99%